(untitled) (Experimental biology, 2015)
In the article gives information on the impact on non-target arthropod fauna insecticides konfidor extra, w.d.g. and mospilan 20%, s. p. Insecticides used to protect plants from pests can have a significant impact on the ecosystem as a whole and non-target arthropod fauna in particular. Impact of drugs used for this part of the ecosystem depends on its chemical class. Total counts were collected in the 9702 instance arthropods belonging to 53 families and 10 orders of insects and spiders. Noted that insecticides Konfidor extra and Mospilan no appreciable negative effect on the insect fauna of the grass, but reduce the number of spiders.